Magnitude effect in intertemporal allocation tasks - Chen Sun; Jan Potters (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We investigate how intertemporal allocation of monetary rewards is influenced by the size of total budget, with a particular interest in the channels of influence. We find a significant magnitude effect: the budget share allocated to the later date increases with the size of the budget. At the aggregate level as well as at the individual level, we find magnitude effects both on the discount rate and on intertemporal substitutability (i.e. utility curvature). The latter effect is consistent with theories in which the degree of asset integration is increasing in the stake.
Keywords: C91; D12; D91; 330; time preference; magnitude effect; Convex Time Budget method